Ethics in social networking and business 2 the future and changing paradigms - Massotte, Pierre (Wiley-ISTE, 2017)
Annotation
Includes bibliographical references and index. - CIP data; resource not viewed
Keywords: Business enterprises -- Computer network resources; Business networks; Social Networking; Réseaux d'affaires; BUSINESS & ECONOMICS; Business Ethics; Business enterprises; Computer network resources; Internet Resources